2011
DOI: 10.1007/s00419-011-0561-9
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear microbeam model based on strain gradient elasticity theory with surface energy

Abstract: A microscale nonlinear Bernoulli-Euler beam model on the basis of strain gradient elasticity with surface energy is presented. The von Karman strain tensor is used to capture the effect of geometric nonlinearity. Governing equations of motion and boundary conditions are obtained using Hamilton's principle. In particular, the developed beam model is applicable for the nonlinear vibration analysis of microbeams. By employing a global Galerkin procedure, the ordinary differential equation corresponding to the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…As Mindlin demonstrated that such a 3 theory is able to describe the surface tension for solids, this paper is intended to derive a tractable beam theory based on such a higher order material description. This contribution may therefore be seen as an extension of the recent propositions to describe the behavior of tiny Euler-Bernoulli [11][12][13] or Timoshenko [14] beams. The basic assumptions regarding the beam behavior are first presented.…”
Section: Introductionmentioning
confidence: 85%
“…As Mindlin demonstrated that such a 3 theory is able to describe the surface tension for solids, this paper is intended to derive a tractable beam theory based on such a higher order material description. This contribution may therefore be seen as an extension of the recent propositions to describe the behavior of tiny Euler-Bernoulli [11][12][13] or Timoshenko [14] beams. The basic assumptions regarding the beam behavior are first presented.…”
Section: Introductionmentioning
confidence: 85%
“…It is not Later, Lazopoulos and Lazopoulos [17] used the same strain energy density and developed a linear Timoshenko beam model. Rajabi and Ramezani [18] used this strain energy to construct a non-linear Bernoulli-Euler beam model, and investigated the non-linear free vibration of microbeams.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmadi and his associates [34] studied the buckling of rectangular flexural microplates using the MCST. Based on the SGT with the inclusion of surface energy, Rajabi and Ramezani [35] developed a nonlinear Euler-Bernoulli beam model for the vibration of microbeams. Ansari et al [36] employed the SGT to study the nonlinear vibration of Timoshenko microbeams.…”
Section: Introductionmentioning
confidence: 99%